Behavior of concrete beams reinforced with low ratio of flexural steel reinforcement - Mohammed, Azad A.; Assi, Dunyazad K.; Abdulrahman, Alan S. (Journal of Structural Engineering, 2024)
Properties of high strength concrete other than compressive strength may not enhance in parallel with the compressive strength improve, and such properties need to be assessed carefully before wide practical applications of such type of concrete. Among the important properties one can consider the flexural behavior of concrete beams reinforced with low amount of steel bars. In this paper flexural strength and deformation of concrete beams made from different grades of concrete strengths, reinforced with steel bars close to minimum steel ratio given by codes of practice, were studied. For this purpose six reinforced concrete beams were cast and tested. According to the obtained results any HSC beam reinforced with low amount of steel reinforcement close to the minimum steel ratio provided by ACI code behaves like normal concrete beams except that beam made from concrete with compressive strength equal to 90 MPa. Load capacity and ductility of this type of beam was found to be normal, but fracture of reinforcement was occurred after excessive deflection. Such behavior should be considered in the design of high strength concrete beams with low amount of steel reinforcement.